A comparative study on stability, thermal conductivity, and rheological properties of nanolubricant using carbon-based additive - Puspitasari, Poppy; Permanasari, Avita Ayu; Habibi, Ilham Akbar; Pramono, Diki Dwi; Abdullah, Muhammad Ilman Hakimi Chua (Malaysian Tribology Society (Mytribos), 2024)
This study investigates different thermophysical properties of lubricants added with fullerene, graphene, single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes nanoparticles, with engine oil 10W-30 as the basic fluid. The samples of nanoparticles were prepared in 0.1wt% using two stages synthesis method. Further, we examined the nanoparticle’s morphology, as well as the nanolubricants stability, viscosity, and thermal conductivity. Results show that the SWCNT has the smallest particle size then other nanoparticles. All nanolubricants stable after 3 days sonication. The dynamic viscosity test results show that the lubricant with MWCNTs has the highest viscosity, because the entangled structure of MWCNTs increases surface interaction, when dispersed in the fluid. The results of the thermal conductivity test on fullerene, graphene, SWCNT, DWCNT, and MWCNT nanolubricant indicate increasing thermal conductivity compared with base oil. The shape and size of nanoparticles affect thermal conductivity, cylindrical (Single-walled Carbon Nanotubes, Double-walled Carbon Nanotubes, and Multi-walled Carbon Nanotubes) and buckyball (Fullerene) structures have better thermal conductivity enhancement compared to platelet structure (Graphene). The shape, structure and size of the particles have an influence on stability, viscosity and thermal conductivity.